Implementation of the Intelligence Unit Mobilization to Prevent Silat School Conflicts PSHT and PSHW at Madiun Police - Pratama, Rangga Ridho (Advances in Police Science Research Journal, 2024)
Madiun Regency is one of the historical centers of pencak silat in Indonesia with 14 organizations. PSHT and PSHW are the largest organizations in Madiun Regency that often conflict and disturb public order. Preventive efforts are needed by Sat Intelkam Polres Madiun with intelligence gathering. This research uses a descriptive qualitative approach with field research methods. This research uses SWOT Theory and management accompanied by the Concept of Implementation, Conflict Concept, Police Intelkam Unit Concept, POAC Management Concept, and Intelligence Concept. The results showed that the condition of the Intelkam Unit in carrying out intelligence gathering on PSHT and PSHW organizations was optimal. Factors that influence its success include human resources, budget ceiling allocation, facilities and infrastructure, methods used, and cross-sector cooperation. The hindering factors are targets and community support. The implementation of intelligence gathering has been well organized from planning to controlling. The author recommends fostering partnerships with silat leaders and encouraging silat members to maintain public order.